2021
DOI: 10.1063/5.0038761
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid identification and tracking of Lagrangian mesoscale eddies

Abstract: Automatic identification and tracking of mesoscale eddies are crucial in large oceanic observational and numerical model data. This work proposes a fully automated method that identifies and tracks from a single Lagrangian advection, all mesoscale eddies, without prior knowledge of their lifespans. The eddies' detection and tracking use a hybrid method based on geometrical properties of the evolving velocity along Lagrangian trajectories and a grid density-based clustering algorithm. The high eddies' monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Moreover, a Lagrangian point of view has been used to detect Coherent Lagrangian Vortices. Different methodologies were developed to detect mesoscale eddies through direct considerations on advected fields or particles evolving together in time, in particular to reduce the number of thresholds commonly used in Eulerian methods (Abernathey and Haller, 2018;Beron-Vera et al, 2008;El Aouni, 2021;Haller, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a Lagrangian point of view has been used to detect Coherent Lagrangian Vortices. Different methodologies were developed to detect mesoscale eddies through direct considerations on advected fields or particles evolving together in time, in particular to reduce the number of thresholds commonly used in Eulerian methods (Abernathey and Haller, 2018;Beron-Vera et al, 2008;El Aouni, 2021;Haller, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have investigated lifetimes in the context of ocean eddies, for example, Froyland et al [20] first identified a suitable timescale and then carried out a series of FTCS computations on time windows sliding forward in time, Andrade et al [3] exhaustively search a discretised twoparameter space (𝑡, 𝑇) where 𝑡 is the initial time and 𝑇 is the flow duration, using these pairs as variable inputs to many separate LCS computations. El Aouni [14] identifies the timespans of local rotational motion during each Lagrangian trajectory and then defines an eddy as those trajectories that are close at the beginning and the end of their respective timespans.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed comparisons show that all Eulerian methods have pros and cons, and none of them is superior to another (Souza et al, 2011;Escudier et al, 2016). Methods based on identifying Lagrangian coherent structures obey a much better mathematical foundation (Haller, 2015;Beron-Vera et al, 2018;Haller et al, 2018;El Aouni, 2021;Ryzhov and Berloff, 2022). However, they are computationally rather demanding and the (relatively low) spatial resolution of the input fields is a challenging aspect of them (Amores et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1. Recent data evaluation of satellite observations suggests that eddy-rich regions exhibit a significant increase in mesoscale variability (thus EKE per unit volume), while the equatorial oceans show a decrease in EKE (Martínez-Moreno et al, 2019, 2021.…”
Section: Introductionmentioning
confidence: 99%